Long-Term Effects of the University of Wisconsin--Eau Claire Civil Rights Pilgrimage - Thesing-Ritter, Jodi; Walkowiak, Nicholas; Vruwink, Madeleine; Lewis, Cecelia; Jones, Jacie; Edwardson, David; Anthony, Kelly (My University, 2018)
The Civil Rights Pilgrimage (CRP) is an immersion experience that has been offered 20 times with 1206 total participants available for study. Participants go on a ten-day pilgrimage, visiting key historical locations of the civil rights movement, touring museums, and speaking with influential foot soldiers. Anecdotally, many participants report a life-changing experience, bringing what they learned back to the University of Wisconsin-Eau Claire and into their own lives. In order to understand the CRP’s impact, we will investigate how or if the CRP has changed participants’ lives one to ten years after the experience by acquiring descriptive research. This research supports the claim that cultural immersion experiences have a positive and lasting impact (https://www.aacu.org).
Color poster with text and bar graphs.
Keywords: Posters; Civil Rights Pilgrimage (Eau Claire, Wis.); Racism--Wisconsin--Eau Claire--Measurement